Impaired mucus clearance exacerbates allergen-induced type 2 airway inflammation in juvenile mice - Fritzsching, Benedikt; Hagner, Matthias; Christochowitz, Sandra; Agrawal, Raman; Bodegom, Charlotte van; Schatterny, Jolanthe; Hirtz, Stephanie; Brown, Ryan; Dürr, Julia; Zhou-Suckow, Zhe; Mall, Marcus A. (The journal of allergy and clinical immunology, 2017)
Type 2 airway inflammation plays a central role in the pathogenesis of allergen-induced asthma, but the underlying mechanisms remain poorly understood. Recently, we demonstrated that reduced mucociliary clearance, a characteristic feature of asthma, produces spontaneous type 2 airway inflammation in juvenile β-epithelial Na+ channel (Scnn1b)-transgenic (Tg) mice.